Informal, Entrepreneurial, or Precarious Work? The Life Trajectory of Street Food Micro-Business Owners - Nogueira Pinheiro de Oliveira, Eveline (2022)
Objective. This research aimed to understand and analyze the entrepreneurial activity of formal and informal micro-business owners involved in the street food segment in the city of Fortaleza, State of Ceará / Brazil. Method. 10 street food micro-business owners from the city of Fortaleza, aged between 25 and 73 years old, among them sellers of hot dogs, corn, tapioca, pastries, and other types of food products, were interviewed, using semi-structured interviews. Results. One characteristic that becomes paramount for contemporary street food micro-business owners is that of being an entrepreneur. The lack of a career perspective in the formal job market makes the micro-business owners regard the street food segment as a kind of salvation from that context, and convey entrepreneurial ideas focused on informality, which ultimately reinforce precariousness processes.